A review on multifunctional aerogel fibers: processing, fabrication, functionalization, and applications. (March 2022) - Tafreshi, O.A.; Mosanenzadeh, S.G.; Karamikamkar, S.; Saadatnia, Z.; Park, C.B.; Naguib, H.E.
Abstract: Aerogels have been frequently reported in three-dimensional (3D) monolith bulk, granule, and two-dimensional (2D) thin-film geometries. However, their commercialization has been widely restricted due to the lack of flexibility, extensibility, and fragile network structures. Recently, a new class of aerogels, i.e. aerogel fibers has emerged. When conventional aerogels are transformed into fibers (sub-micron or nanofibers), their performance may enhance remarkably. Therefore, such aerogel fibers can exhibit improved mechanical performance, favorable flexibility, higher tensile strength, and enhanced extensibility. This will make them a suitable candidate for applications that require high mechanical flexibility and to be stretchable. In conjunction with the superior thermal insulation performance of aerogels, aerogel fibers can be extensively used in other commercial sectors where load-bearing is crucial. In this short review, we intend to assess the current technologies for the production of aerogels in fiber geometry, called "aerogel fiber." Materials used for this purpose, along with the post-processing and functionalization methods, are also evaluated. Their recent breakthroughs in emerging applications in a variety of engineering fields are covered. A discussion of current challenges, limitations, and the urgent need for the development of new technologies for the continuous production of aerogel fibers is provided. A road map pointing to a future direction in aerogel fiber field will be discussed. Graphical abstract: Image 1 Highlights: Exploration of the aerogel fibers as an emerging class of aerogel materials. The aerogel fibers processing technologies, materials, and functionalization. Intrinsic limitations and challenges associated with the aerogel fiber development. Overview of the aerogel fibers application in various engineering fields.